Understanding context : environment, language, and information architecture - Hinton, Andrew (O'Reilly, 2014)
"This practical, insightful book provides a powerful toolset to help information architects, UX professionals, and web and app designers understand and solve the many challenges of contextual ambiguity in the products and services they create. You'll discover not only how to design for a given context, but also how design participates in making context. Learn how people perceive context when touching and navigating digital environments. See how labels, relationships, and rules work as building blocks for context. Find out how to make better sense of cross-channel, multi-device products or services. Discover how language creates infrastructure in organizations, software, and the Internet of Things. Learn models for figuring out the contextual angles of any user experience"--Back cover.
Keywords: Interpersonal communication; Communication : Study and teaching; Information storage and retrieval systems : Architecture; Web sites : Design; informaatio; verkkoympäristö; sosiaalinen vuorovaikutus; verkkosivustot; tiedonhallinta; tiedonhallintajärjestelmät; käyttöliittymät; suunnittelu; information; onlinemiljö; social interaktion; webbplatser; informationshantering; datahanteringssystem; användargränssnitt; planering